Definitional Snag in Anti-rape Laws in Bangladesh: A Comparative Note - Nigar, Meher (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
In Bangladesh, rape is the most extreme form of sexual violence which destroys a women’s life. Bangladesh, in line with its constitutional commitment, guarantees equal protection of law, and it guarantees freedom of movement for all subject to law by creating a violence free society for women. To this end, several laws are in place to deal with rape related crimes which contains strict punishment including death penalty. Despite having specific legal regime, rape incidence has been increasing at an alarming rate in Bangladesh. In this context, this article aims to study gaps that persist in existing anti-rape laws in Bangladesh. Acknowledging the fact that there are many procedural and practical challenges in the area of anti-rape laws, this article studies the definitional dilemma of ‘rape’ and its limited scope leaving many other types of rape beyond the legal coverage remains a big concern to ensure access to justice for rape victims. To expand legal protection to victims, this article examines the normative gaps in existing definitions of rape, studies contemporary legal developments in this area in other subcontinent countries, and concludes with suggestion that major definitional reforms are necessary in rape laws in Bangladesh.